Rahn Tasjily Product Development Strategy at PT. Pegadaian (Persero) Sharia Service Unit Mandailing Natal - suaibah suaibah; arbanur rasyid; adanan murrah; rahmat annam (Journal Of Sharia Banking, 2021)
The background of the problem in this study is that the product development strategy rahn tasjily has been implemented well with evidence that there are some customers who have become customers of tasjily rain products, but the process in increasing the number of customers has still not increased. The formulation of this research problem is how the product development strategy rahn tasjily at PT. Pegadaian (Persero) Sharia Service Unit Mandailing Natal, any obstacles in developing the number of customers of rahn tasjily products at PT. Pegadaian (Persero) Sharia Service Unit Mandailing Natal. This research uses qualitative approaches with data collection techniques in the form of interview guidelines, observation and documentation, data reduction analysis techniques, data presentation, and conclusion withdrawal. The subject of this study is the leadership and employees of PT. Pegadaian (Persero) Unit of Sharia Services Mandailing Natal and customers as many as 4 people, the data source used is primary data and secondary data. The results showed that rahn tasjily product development strategy in PT. Pegadaian (Persero) Mandailing Natal Sharia Service Unit is a marketing mix that is one of them with promotion through social media, direct promotion, jumping into the field, and socialization. The strategy has not increased because the public does not know the product rahn tasjily well. Constraints of PT. Pegadaian (Persero) Sharia Service Unit Mandaiiling Natal in marketing products to improve there are some of the promotions that are done less, lack of socialization, limited operational costs. And the assumption of the community that pawnshops only as a place to pawn money.